Jacobson and Truax Method: evaluation of the clinical effectiveness of a home care program after prostatectomy - Luciana Regina Ferreira Pereira da Mata; Mariana Ferreira Vaz Gontijo Bernardes; Cissa Azevedo; Tânia Couto Machado Chianca; Maria da Graça Pereira; Emilia Campos de Carvalho (Universidade de São Paulo, 2018)
ABSTRACT Objective: to exemplify the applicability of the Jacobson and Truax Method in a nursing intervention study that analyzed the effectiveness of a home care teaching program after radical prostatectomy. Method: this is a descriptive study concerning the applicability of the Jacobson and Truax Method in the data analysis of a clinical trial. The intervention consisted of a teaching program for hospital discharge after radical prostatectomy through oral guidance, writing, and telephonic reinforcement. Thirty-four men participated in the intervention group and 34 men participated in the control group. A reliable index of change and clinical significance was calculated for the knowledge variable in both groups. Scatterplots were presented to demonstrate the effectiveness of the method. Results: for 30 individuals in the intervention group, the intervention presented clinically relevant change than in knowledge. In the control group, none of the 34 individuals presented clinical significance of the results related to this variable, that is, the statistical significance identified by the inferential tests did not have clinically relevant changes in the knowledge variable. Conclusion: the educational intervention carried out through the combination of oral, written and telephone counseling was shown to be clinically effective in improving knowledge about home care.